2013
DOI: 10.1089/humc.2013.168
|View full text |Cite
|
Sign up to set email alerts
|

Intrapleural Administration of an AAVrh.10 Vector Coding for Human α1-Antitrypsin for the Treatment of α1-Antitrypsin Deficiency

Abstract: Alpha-1 antitrypsin (α1AT) deficiency is a common autosomal recessive disorder characterized by a marked reduction in serum α1AT levels, lung and liver disease. α1AT is mainly produced and secreted by hepatocytes, with its primary function to protect the lung against the proteolytic activity of neutrophil elastase. Serum α1AT levels <11 μM are associated with progressive destruction of lung parenchyma and early-onset of panacinar emphysema in the age range 35-45. The current approved treatment for α1AT deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 47 publications
1
33
0
1
Order By: Relevance
“…Importantly, similar levels were achieved in serum lung ELF, demonstrating "biochemical efficacy." In a safety and toxicology study, the AAVrh.10 delivered by the intrapleural route was shown to be safe in studies with 280 mice and 36 nonhuman primates (149). The intrapleural vector transfer resulted in high levels of human AAT messenger RNA localized to the proximity of the lung that persisted for at least 6 months in mice (149) and for at least 1 year after a single vector administration in nonhuman primates (149), the entire length of the study ( Figure 6).…”
Section: C/fpomentioning
confidence: 97%
See 1 more Smart Citation
“…Importantly, similar levels were achieved in serum lung ELF, demonstrating "biochemical efficacy." In a safety and toxicology study, the AAVrh.10 delivered by the intrapleural route was shown to be safe in studies with 280 mice and 36 nonhuman primates (149). The intrapleural vector transfer resulted in high levels of human AAT messenger RNA localized to the proximity of the lung that persisted for at least 6 months in mice (149) and for at least 1 year after a single vector administration in nonhuman primates (149), the entire length of the study ( Figure 6).…”
Section: C/fpomentioning
confidence: 97%
“…In the case of parietal pleura, the lymphatic system connects directly to the pleural space through stomata, a mechanism for systemic distribution of the gene therapy vector to primarily the liver after intrapleural delivery ( Figure 4A) (138,139,148). Another advantage of targeting the pleura for gene therapy is the low risk of adverse effects of any inflammation induced by the gene therapy vector, as demonstrated in a safety and toxicology study (149).…”
Section: C/fpomentioning
confidence: 99%
“…Other modifications have focused on the promoter, method, and optimal application site to supply a high level of transgene expression. 66,67,[70][71][72][73][74][75][76][77] Efficiency of AAT expression at the rAAV application site. The first study using rAAVs in AATD was conducted in 1998.…”
Section: Aav Vectors In Aatd Gene Therapymentioning
confidence: 99%
“…76 The preclinical study demonstrated that intrapleural administration of the carrier allowed for the detection of AAT mRNA for 6 months in 280 mice and 1 year in 36 nonhuman primates, with no side effects. 77 AAVs in AATD experimental treatment: summary. Numerous studies have demonstrated that the therapeutic effect depends on multiple factors, such as AAV serotype, prior exposure to virus, and administration site.…”
Section: Aav Vectors In Aatd Gene Therapymentioning
confidence: 99%
“…Another strategy to decrease the immune response might be to select or create a capsid type with lower preexisting immunity or immune profile in humans. 39,40,41 Expression could be potentially increased through codon optimization of the AAT gene or through the use of selfcomplimentary AAV vectors.…”
Section: Future Directionsmentioning
confidence: 99%